Trial of labor in women with previous cesarean section - Huertas Tacchino, Erasmo (2015)
Background: The absolute and relative risks associated with the trial of labour in women with previous cesarean section have led to an increase in the rate of caesarean sections, despite the evidence that demonstrates the safety and benefits of trial of labour. Objectives: To determine maternal and perinatal outcomes of pregnant women with prior cesarean section to whom trial of labor was indicated. Design: Cohorts, retrospective, analytical study. Setting: Fetal Medicine Unit, Instituto Nacional Materno Perinatal, Lima, Peru. Participants: Pregnant women with prior cesarean section and attended at their delivery. Interventions: We reviewed clinical records of 584 women with history of previous cesarean section who delivered at Instituto Nacional Materno Perinatal between January and December 2007. We excluded patients who did not meet inclusion criteria and reviewed outcomes of the remaining 266. Main outcome measures: Maternal and perinatal outcomes. Results: From 266 pregnant women with one previous C-section and no contraindications for vaginal delivery 188 (70.7%) had indication of repeat cesarean section and 78 (29.3%) had trial of labor, successful in 51 (65.3%). In the elective cesarean group there was one uterine rupture, one hysterectomy, and two post-partum hemorrhages. In the trial of labour group there were no uterine ruptures, hysterectomies, post-partum hemorrhage. There were no maternal deaths in any group as well as any antepartum or intrapartum intrauterine death, Apgar score below 7 at 5 minutes or neonatal deaths. Conclusions: There was no statistical significant difference in perinatal and maternal outcomes in pregnant women with previous C-section who had trial of labour compared with those who had elective repeated cesarean section. The success rate of trial of labour group was 65.3%.